On the growth of deformations of algebras associated with Coxeter graphs - Popova, N. D.; Samoilenko, Yu. S.; Strilets, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We investigate a class of algebras that are deformations of quotient algebras of group algebras of Coxeter groups. For algebras from this class, a linear basis is found by using the “diamond lemma.” A description of all finite-dimensional algebras of this class is given, and the growth of infinite-dimensional algebras is determined.